MANAGING TRI PUSAT PENDIDIKAN IN THE COVID -19 PANDEMIC - Tyas, E. Handayani; Naibaho, Lamhot (International Journal of Research -GRANTHAALAYAH, 2021)
This study is about the management of Tri Pusat Pendidikan in the COVID-19 Pandemic. This study aims to find out the management of Tri Pusat Pendidikan strictly in the current situation, namely COVID-19. It was done at Universi- tas Kristen Indonesia within three months, from January – March 2021. The method of the study used as library research, and the instrument used in this study was a checklist document used to record offline or online documents sourced from books, papers, journals and articles taken from Google Scholar. The documents taken are documents that examine the management of the Tri Pusat Pendidikan, as also discussed in this study. The result of the study is that as the critical success of educating children, Tri Pusat Pendidikan should be well managed by conducting a better collaboration among teachers, parents, the community involved in education program implementation, and the learn- ing process during the COVID-19 Pandemic must remain sustainable.